CONCEPT OF ISLAMIC EDUCATION PSYCHOLOGY IN IHYA’ ‘ULUM AL-DIN BY AL-GHAZALI - Khairina Siregar (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
The concept of Islamic education psychology in Al-Ghazali's Ihya' 'ulum al-din is a tazkiyah an-Nafs effort that is taken through learning. This study aims to analyze the concept of Islamic education psychology in the book Ihya' 'ulum al-din through modern educational psychology theories and the impact of their application on the psychology of Islamic education today. This research uses a qualitative approach with a literature study method. Analysis, data sources and testing the validity of research data through reference materials (scientific). The results of this study indicate that the results of this study indicate that (1) the psychological concept of Islamic education contained in the book Ihya 'Ulum al-Din hints at the integrity and balance between science, educators and students as potential "spirits" to change one's behavior or character. (2) the psychology of Islamic education in the book Ihya 'Ulum al-Din has an influence on the world of psychology in general. This is tested through analysis of modern theories, namely behaviorism, psychoanalysis, humanistic and transpersonal. (3) The potential of the book Ihya 'Ulum al-Din and its contribution to contemporary psychology is considered to be very large. This can be seen from the efforts to balance and the principle of integrity between science, educators and students and help analyze the phenomena of Islamic education from the beginning in a psychological perspective. This is tested through analysis of modern theories, namely behaviorism, psychoanalysis, humanistic and transpersonal. (3) The potential of the book Ihya 'Ulum al-Din and its contribution to contemporary psychology is considered to be very large. This can be seen from the efforts to balance and the principle of integrity between science, educators and students and help analyze the phenomena of Islamic education from the beginning in a psychological perspective. This is tested through analysis of modern theories, namely behaviorism, psychoanalysis, humanistic and transpersonal. (3) The potential of the book Ihya 'Ulum al-Din and its contribution to contemporary psychology is considered to be very large. This can be seen from the efforts to balance and the principle of integrity between science, educators and students and help analyze the phenomena of Islamic education from the beginning in a psychological perspective.